Electromagnetic contactless torque transducer: torque measurement and shaft impediment approach - Rahman, Mohammed Ataur; Mohiuddin, A. K. M.; Md Daud, Badrul (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
The torque transducer is important to measure the torque on a rotating power transmission system such as engine crankshaft, transmission, motor shaft, and bicycle crank. Static torque is relatively easy to measure but dynamic torque is difficult to measure, since it requires transferring some torsional effect in terms of electric signal or magnetic inductive voltage. The several torque transducers has been made with slip ring and metallic resistance strain gauges to measure the dynamic torque of the power transmission shaft. However, the slip ring method brushes are prone to wear and tear and need to be replaced frequently while the strain gauge chemical properties is disturbed due to heat and provided the significant error of the signal output which emphasis this study to develop an electromagnetic non-contact (EMNC) torque transducer to measure the dynamic torque of the power transmission shaft. The EMNC torque transducer has been made from this study with a permanent magnet and two cylindrical coils. The first coil serves as the electromagnet, which causes the force (attractive) and second coil gets the voltage induction due to the changing of the magnetic field. The measured voltage of the second coil represents the torque applied on the shaft.